Research on cryosestic communities in Svalbard: the snow algae of temporary snow fields in Petuniabukta, Central Svalbard - Kvíderová, J. (Jana) (2012)
Although observations of cryosestic communities in Svalbard could be dated to 17th century, no observations were reported from Petunuiabukta till 2009. Two possible cryosestic habitats were recognized there - temporal snow fields that melt-away in summer completely, and perennial glacier sirfaces. During summer seasons 2009 - 2011, ten temporal snow fields were sampled and cryosestic communities studied. In the samples, zygospores of Chlamydomonas cf. nivalis vere dominant. Other found species included Chloromonas nivalis, Cryodactylon glaciale and cf. Chainomonas sp.